Juno Plasma Wave Observations at Ganymede. Issue 23 (12th December 2022) - Kurth, W. S.; Sulaiman, A. H.; Hospodarsky, G. B.; Menietti, J. D.; Mauk, B. H.; Clark, G.; Allegrini, F.; Valek, P.; Connerney, J. E. P.; Waite, J. H.; Bolton, S. J.; Imai, M.; et al.
Abstract: The Juno Waves instrument measured plasma waves associated with Ganymede's magnetosphere during its flyby on 7 June, day 158, 2021. Three distinct regions were identified including a wake, and nightside and dayside regions in the magnetosphere distinguished by their electron densities and associated variability. The magnetosphere includes electron cyclotron harmonic emissions including a band at the upper hybrid frequency, as well as whistler‐mode chorus and hiss. These waves likely interact with energetic electrons in Ganymede's magnetosphere by pitch angle scattering and/or accelerating the electrons. The wake is accentuated by low‐frequency turbulence and electrostatic solitary waves. Radio emissions observed before and after the flyby likely have their source in Ganymede's magnetosphere. Plain Language Summary: Observations of plasma waves during the Juno flyby of Ganymede on 7 June 2021 provided evidence of a wake region behind the moon as well as two distinct regions within Ganymede's magnetosphere. Some narrowband wave features enabled the determination of the density of electrons in the magnetosphere. Other intense emissions known as chorus and hiss likely interact with energetic electrons and may be at least partially responsible for auroras seen on the moon. Radio waves detected near Ganymede are likely generated in its magnetosphere. Key Points: Whistler‐modes, electron cyclotron harmonics, upper hybrid band and radio emissions are detected in and near Ganymede's magnetosphere Three distinct regions in and near the magnetosphere are observed, wake, nightside, and dayside The dayside ionosphere exhibits higher and more variable electron densities than does the nightside